Social work and community practice - Palmer, Sharon Duca, 1965- (Oakville, Ont. : Apple Academic Press, 2011)
Explores a variety of physical, mental, and lifestyle challenges faced by community populations, including homelessness, community health promotion, nutrition intervention, smoking trends among certain populations, mental health issues among different age and gender groups, substance abuse, domestic violence, contraception, and more.
Includes bibliographical references and index.
Keywords: Community-based social services; Medical social work